CD248 and integrin alpha-8 are candidate markers for differentiating lung fibroblast subtypes - Matsushima, Sayomi (BMC Pulm Med, 2020)
BACKGROUND: Lung fibrosis is a serious life-threatening condition whose manifestation varies according to the localization and characteristics of fibroblasts, which are considered heterogeneous. Therefore, to better understand the pathology and improve diagnosis and treatment of this disease, it is necessary to elucidate the nature of this heterogeneity and identify markers for the accurate classification of human lung fibroblast subtypes. METHODS: We characterized distinct mouse lung fibroblast subpopulations isolated by fluorescence-activated cell sorting (FACS) and performed microarray analysis to identify molecular markers that could be useful for human lung fibroblast classification. Based on the expression of these markers, we evaluated the fibroblast-like cell subtype localization in normal human lung samples and lung samples from patients with idiopathic pulmonary fibrosis (IPF). RESULTS: Mouse lung fibroblasts were classified into Sca-1(high) fibroblasts and Sca-1(low) fibroblasts by in vitro biological analyses. Through microarray analysis, we demonstrated CD248 and integrin alpha-8 (ITGA8) as cell surface markers for Sca-1(high) fibroblasts and Sca-1(low) fibroblasts, respectively. In mouse lungs, Sca-1(high) fibroblasts and Sca-1(low) fibroblasts were localized in the collagen fiber-rich connective tissue and elastic fiber-rich connective tissue, respectively. In normal human lungs and IPF lungs, two corresponding major fibroblast-like cell subtypes were identified: CD248(high)ITGA8(low) fibroblast-like cells and CD248(low)ITGA8(high) fibroblast-like cells, localized in the collagen fiber-rich connective tissue and in the elastic fiber-rich connective tissue, respectively. CONCLUSION: CD248(high)ITGA8(low) fibroblast-like cells and CD248(low)ITGA8(high) fibroblast-like cells were localized in an almost exclusive manner in human lung specimens. This human lung fibroblast classification using two cell surface markers may be helpful for further detailed investigations of the functions of lung fibroblast subtypes, which can provide new insights into lung development and the pathological processes underlying fibrotic lung diseases.